Effects of temperature and time treatment on soil characteristics and wheat growth - Guo, Zhen; Han, Jichang; Zhang, Yang; Zhuang, Hua (Frontiers in Sustainable Food Systems, 2025)
The application of exogenous heating as a physical method to improve soil quality has a significant impact on agricultural ecosystems. In this study, we conducted surface soil heating treatments at two temperatures (80 °C and 210 °C) and four time scales (2 s, 6 s, 10 s, and 15 s) using natural temperature as a control. The aim was to evaluate the multiple effects on soil nutrients, wheat growth, and microorganisms. This study mainly consisted of a pot experiment, which was conducted from October 2022 to January 2023. The loess used in the experiment was taken from degraded farmland in Baqiao District, Shaanxi, and the experiment was carried out in the core experimental area of soil organic reconstruction in Shaanxi. The results showed that compared to 210 °C treatment, soil organic matter, available potassium, and active organic carbon increased by 3.14%, 1.42%, and 5.88%, respectively, under the 80 °C treatment, altering the soil nutrient status. The combined effects of temperature and time enhanced both above-ground and root growth characteristics of wheat. The 210 °C treatment also facilitated a reduction in soil clay content. The relative abundance of Acidobacteriota and Chloroflexi generally increased across all treatments. Long-duration treatment at 80 °C significantly increased microbial richness. The clay content and available phosphorus had a substantial impact on microbial communities, with a significant negative correlation between clay content and Chloroflexi. Short-duration treatment at 210 °C significantly enhanced bacterial amino acid transport and ribosome structural function abundance. These findings suggest that exploring the application of exogenous heating methods can promote the development of green agriculture and the health of soil ecosystems.